Simulasi Docking Molekuler Senyawa Xanthorrhizol sebagai Antiinflamasi terhadap Enzim COX-1 dan COX-2 - Deden Indra Dinata; Hardhi Suryatno; Ida Musfiroh; Shelvy E Suherman (Indonesian Journal of Pharmaceutical Science and Technology, 2014)
There are two enzymes that influence inflammatory process, which are COX-1 and COX-2 enzymes, have function in the establishment of prostaglandin that contribute in inflammation. Xanthorrhizol has anti-inflammatory effect, so it can be developed and tested by docking simulation to COX-1 and COX-2 enzymes. The aim of this research is to determine the interaction between xanthorrhizol that is derived from Curcuma xanthorriza with the active site of COX-1 and COX-2 enzymes. Docking simulation was done by using AutoDock Tools 4.0. The interactions between xanthorrhizol with COX-1 are O- xanthorrhizol interact with Arg120 and Tyr355. The interactions between xanthorrhizol with COX-2 are OH-xanthorrhizol interact with Gln178 and Leu338. Leu338 is specific amino acid in the binding pocket of COX-2. Xanthorrhizol can interact with the active site of COX-1 and COX-2 enzymes, show better affinity to COX-2. Keywords: Antiinflamasi, COX-1, COX-2, docking, xanthorrhizol